2008
DOI: 10.1111/j.1743-6109.2007.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Female Genital Vasocongestive Arousal Responses in Young and Aged Rats

Abstract: Introduction Treatments of aged, male hypertensive rats that induce vascular remodeling or that normalize endothelial function are known to produce sustained improvements in erectile function. Whether the treatments targeting these processes benefit female genital vasocongestive arousal (GVA) responses is currently not known. Aim To determine whether the actions of nitric oxide (NO) are critical to the apomorphine (APO)-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The presence of a yawning response in the GK rats demonstrates that the drug was successfully administered and that the deficit in sexual responses could be because of an underlying pathology. These results parallel similar observations by Beharry et al where older female rats demonstrated a significant decrease in APO-induced GVAs when compared with young rats [22]. The APO-mediated yawning response that was observed in both Wistar and GK rats was significantly less in the diabetic animal, suggesting that central mediated sexual stimulation may also be altered.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of a yawning response in the GK rats demonstrates that the drug was successfully administered and that the deficit in sexual responses could be because of an underlying pathology. These results parallel similar observations by Beharry et al where older female rats demonstrated a significant decrease in APO-induced GVAs when compared with young rats [22]. The APO-mediated yawning response that was observed in both Wistar and GK rats was significantly less in the diabetic animal, suggesting that central mediated sexual stimulation may also be altered.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies have revealed that select antihypertensive treatments have improved erectile function in hypertensive rats and in humans [30–33]. In particular, drugs that antagonize the renin‐angiotensin system are associated with improved endothelial function, decreased type III collagen in corpora cavernosum and improved erectile function in hypertensive male rats and genital vasocongestive arousal responses in female rats [32,34–36]. Despite this functional evidence, the impact of these changes on the morphology of the pudendal artery, a key resistance vessel, remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, female sexual dysfunction has attracted much interest in the field of medical sciences [2–10]. Female sexual dysfunction, which consists of multiple disorders, are categorized as hypoactive sexual desire disorder, orgasmic disorder, sexual arousal disorder, and sexual pain disorder [2,5,6,11–14]. Female sexual arousal disorder refers to a lack of responsiveness to sexual stimulation in women [15].…”
Section: Introductionmentioning
confidence: 99%